2021
DOI: 10.1155/2021/9950131
|View full text |Cite
|
Sign up to set email alerts
|

A Review of 3D Printing in Dentistry: Technologies, Affecting Factors, and Applications

Abstract: Three-dimensional (3D) printing technologies are advanced manufacturing technologies based on computer-aided design digital models to create personalized 3D objects automatically. They have been widely used in the industry, design, engineering, and manufacturing fields for nearly 30 years. Three-dimensional printing has many advantages in process engineering, with applications in dentistry ranging from the field of prosthodontics, oral and maxillofacial surgery, and oral implantology to orthodontics, endodonti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
143
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(234 citation statements)
references
References 144 publications
(193 reference statements)
1
143
0
2
Order By: Relevance
“…The authors suggested and attributed this result to the shrinkage that the material undergoes during construction and post-production. In turn, they attributed this to the manipulation of data in the STL file, where conversion and formatting were generated and could result in changes [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested and attributed this result to the shrinkage that the material undergoes during construction and post-production. In turn, they attributed this to the manipulation of data in the STL file, where conversion and formatting were generated and could result in changes [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Other specific applications are related, for example, to prosthodontics (e.g., production of crown and bridge dentures, complete dentures, removable partial denture frameworks, etc. ), oral implantology (e.g., production of custom trays and surgical guides for implants' positioning) and oral/maxillofacial surgery (e.g., for the production of occlusal splints, surgical implants, prostheses) [23,35].…”
Section: Production Of the Appliancementioning
confidence: 99%
“…denture frameworks, etc. ), oral implantology (e.g., production of custom trays and surgical guides for implants' positioning) and oral/maxillofacial surgery (e.g., for the production of occlusal splints, surgical implants, prostheses) [23,35].…”
Section: Production Of the Appliancementioning
confidence: 99%
“…The distinctive feature of DLP technology is the diversity of materials, from thermoplastics to resins and ceramics, even zirconia paste. FDM, one of the cheapest and most popular 3D printing technologies in dentistry, enables using polylactic acid, polycarbonate, polyamide, acrylonitrile-butadiene-styrene copolymers [83].…”
Section: Cad/cam Milled and 3d Printed Removable Denturesmentioning
confidence: 99%